Retelling strategies for comprehending and interpreting short stories - Louis, Santha Mary; Gurdial Singh, Kulwindr Kaur (Journal of Modern Languages, 2017)
Recent trends in literature teaching advocate an integration of literature and language. This necessitates an interactive relationship among the student, text and teacher. This study investigated if retelling strategies will improve form four students' comprehension and interpretation of a short story. Retelling strategies are based on the language-based approach which can make short stories accessible to upper secondary school students through various techniques, procedures and strategies employed in the literature classroom. They are also linked to Oxford's (1989) language learning strategies which are defined as specific actions, behaviours, steps or techniques students use to improve their progress in comprehending, internalizing and using the second language. Ninety students participated in this nineweek study. The participants were chosen based on their form three trial examination and their Penilaian Menengah Rendah (PMR - Lower Secondary Evaluation at Form Three Level) for 2005, and were divided into three levels of proficiency which were high, average, and low. This division into three proficiency levels was to determine if retelling strategies would improve comprehension and interpretation of a short story for proficient and low proficient learners. The ninety participants were taught four retelling strategies which were sequencing, summarizing, paraphrasing and analyzing. They completed four written retellings through four tasks in class using a short story entitled, "The Necklace". A pre-test, post-test, pretest questionnaire and a post-test questionnaire were used for data collection. The pre-test questionnaire asked about their profile, exposure to English language and their difficulties in comprehending and interpreting a short story The post-test questionnaire aimed to find out if the retelling strategies taught to them had helped them answer the post-test questions. Findings from the pre-test and post test revealed that there was improvement in comprehension and interpretation of the short story to the extent that all the 90 participants improved in their comprehension and interpretation of it after obtaining instruction on using the retelling strategies. Another reason for these results was due to the teacher's explanation and teaching of the story to her students for two weeks before the post-test.